Assessment of Liver Function Tests in Children with Typhoid Fever: A Hospital Based Study - Ahmad, Shakil (Journal of Nepalgunj Medical College, 2019)
Background: Typhoid fever is among the most endemic diseases in the tropics and which causes significant morbidity and mortality. It can lead to liver damage if not properly treated. Therefore, the liver function test assessment was conducted in children with typhoid fever. Our study aimed to evaluate the liver function test abnormalities in typhoid fever. Material and methods: This was a prospective observational study conducted at the department of paediatrics, Nepalgunj Medical College and Teaching hospital, Nepalgunj for a period of one year August 2018-July 2019.In the present study total 60 children of Typhoid fever were included on the basis of inclusion and exclusion criteria. On admission a detailed history and complete physical examination was carried out. Routine investigations were also carried out. The diagnosis was confirmed by serum Widal test. Liver function tests were performed i.e. Serum glutamic oxaloacetic transaminase [SGOT] and serum glutamic pyruvic transaminase [SGPT] estimation. Result: In the present study total children were 60 in which 43.33% were boys and 56.66% were girls. Fever was present in all the cases loss of appetite, cough, vomiting was present in majority of cases. On admission, SGOT and SGPT levels were found > 35 IU/L in 26 cases (43.33%) and 34 cases (56.66%) respectively. On discharge after 7 days of antibiotic, majority of patients had SGOT and SGPT levels < 35 IU/L. Conclusion: Our study concluded that on admission of children SGOT and SGPT levels were found > 35 IU/L in 43.33% and 56.66% respectively. On discharge after 7 days of antibiotic, majority of patients had SGOT and SGPT levels < 35 IU/L.